Pea Broth Enhances the Biocontrol Efficacy of Lysobacter capsici AZ78 by Triggering Cell Motility Associated with Biogenesis of Type IV Pilus - Tomada, Selena; Puopolo, Gerardo; Perazzolli, Michele; Musetti, Rita; Loi, Nazia; Pertot, Ilaria (Frontiers in Microbiology, 2016)
Bacterial cells can display different types of motility, due to the presence of external appendages such as flagella and type IV pili. To date, little information on the mechanisms involved in the motility of the Lysobacter species has been available. Recently, L. capsici AZ78, a biocontrol agent of phytopathogenic oomycetes, showed the ability to move on jellified pea broth. Pea broth medium improved also the biocontrol activity of L. capsici AZ78 against Plasmopara viticola under greenhouse conditions. Noteworthy, the quantity of pea residues remaining on grapevine leaves fostered cell motility in L. capsici AZ78. Based on these results, this unusual motility related to the composition of the growth medium was investigated in bacterial strains belonging to several Lysobacter species. The six L. capsici strains tested developed dendrite-like colonies when grown on jellified pea broth, while the development of dendrite-like colonies was not recorded in the media commonly used in motility assays. To determine the presence of genes responsible for biogenesis of the flagellum and type IV pili, the genome of L. capsici AZ78 was mined. Genes encoding structural components an d regulatory factors of type IV pili were upregulated in L. capsici AZ78 cells grown on the above-mentioned medium, as compared with the other tested media. These results provide new insight into the motility mechanism of L. capsici members and the role of type IV pili and pea compounds on the epiphytic fitness and biocontrol features of L. capsici AZ78.